Terrorism and Photojournalism: Sensational Image and Ethical Coverage in the Arab and American Media - Jaber, Fadi (Université d'Ottawa / University of Ottawa, 2011)
During the 2008-2009 War on Gaza between Hamas and Israel, the Arab and American media published various sensational images of this terrorist event. The purpose of this thesis is to investigate and examine the ethicality of the Arab and American sensational images when covering a terrorist event perpetuated by the Other. The thesis draws on Aristotle’s theory of communication and virtue theory (fourth century B.C.), William James’s theory of truth (1907), as well as on contemporary theories, approaches and concepts in order to provide a philosophical and theoretical foundation of ethical publication of sensational images. As well, it looks into various definitions of terrorism, analyzes the Arab and American media codes of ethics, and benefits from relevant decision-making models. It has, therefore, established a theoretical model contingent to the terrorist event at stake – The Sensational Image of Terrorism Ethical Decision-Making Model (SITE-DMM). The thesis methodologically utilizes a qualitative comparative content analysis research design, analyzing a purposive sample of 144 sensational images from three Arab online media (Al-Ahram newspaper, Electronic Intifada, and Al-Jazeera.net TV); and three American online media (The New York Times newspaper, San Francisco Sentinel.com, and CNN.com TV) in order to examine the ethicality of publishing sensational images about this terrorist event in both the Arab and American media. Following a systematic analysis, guided by the suggested theoretical model – SITE-DMM, the findings provide a comprehensive understanding of the ethicality of the Arab and American sensational images during the coverage of the 2008-2009 War on Gaza.
Keywords: Sensational Image; War on Gaza; Arab Media; American Media; Israel; Palestine